(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Micro, Small and Medium Enterprises (MSMEs) in rural India are critical to employment generation and regional economic development, yet they remain largely excluded from the benefits of Artificial Intelligence (AI)‑driven transformation due to a persistent skill gap and low digital literacy. This study evaluates how government‑led digital‑literacy and training programmes—such as PM‑GKAN, PMGDISHA‑linked initiatives, and sector‑specific ICT schemes—have impacted rural MSMEs’ readiness to adopt AI tools in their production and marketing processes. Using a mixed‑methods approach, we find that basic digital‑literacy interventions significantly improve device and internet usage among rural entrepreneurs, but their effectiveness in translating to AI‑specific skills remains limited. The paper argues that targeted AI‑oriented upskilling, contextualised curricula, and stronger linkages between government programmes and local MSME clusters are necessary to bridge the AI skill divide and position rural MSMEs as competitive nodes in India’s digital economy.Artificial Intelligence (AI) is rapidly transforming business operations across the globe, including India’s Micro, Small and Medium Enterprises (MSMEs). However, rural MSMEs continue to face major barriers in adopting AI technologies due to inadequate digital literacy, poor technological infrastructure, financial limitations, and lack of specialized training. This research paper evaluates the effectiveness of government-led digital literacy and AI-oriented training initiatives in bridging the AI skill gap among rural MSMEs in India. The study focuses on schemes such as Pradhan Mantri Gramin Digital Saksharta Abhiyan (PMGDISHA), MSME Technology Centres, Digital India initiatives, and entrepreneurship development programs. A mixed-method research methodology was adopted using secondary data from government reports, policy documents, and recent MSME surveys. The findings reveal that while government programs have significantly improved basic digital awareness and internet usage among rural entrepreneurs, advanced AI adoption remains limited due to insufficient technical mentoring, inadequate infrastructure, and lack of industry-specific AI training. The paper concludes that a stronger integration of AI-focused curriculum, localized training models, public-private partnerships, and continuous support systems is necessary to build a sustainable AI-ready rural MSME ecosystem in India.